Harvesting Prosperity : Technology and Productivity Growth in Agriculture - Fuglie, Keith (Washington, DC: World Bank, 2019)
This book documents frontier knowledge on the drivers of agriculture productivity to derive pragmatic policy advice for governments and development partners on reducing poverty and boosting shared prosperity. The analysis describes global trends and long-term sources of total factor productivity growth, along with broad trends in partial factor productivity for land and labor, revisiting the question of scale economies in farming.